Penicillin-binding components of penicillin-susceptible and -resistant strains of Streptococcus pneumoniae. - Percheson, P B (1980)
Three strains of Streptococcus pneumoniae with low-level resistance to penicillin, one strain with resistance to penicillin, and three strains susceptible to penicillin were compared. The three susceptible strains had very similar patterns of penicillin-binding components (PBCs) as detected by fluorography after sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Gels of these strains showed four major bands and a single minor band. All of the resistant strains showed different PBC patterns from those obtained for susceptible strains. The most marked changes were observed with the most resistant strain SPR110, which showed markedly reduced intensity of PBC 3 and a reduction in intensity of PBCs 1 and 2, as well as additional bands in the region of band 2. Low-level resistant strains had band densities different from the susceptible strains principally for PBC 3. No beta-lactamase activity or plasmid was detected in the resistant strains. An apparent difference in affinity for cloxacillin was also demonstrated between some of the PBCs of susceptible strain S. pneumoniae SPS101 and resistant strain S. pneumoniae SPR110. Penicillin resistance in the low-level resistant and the resistant strains was associated with PBCs possessing different properties from those seen in the three susceptible strains. Reduction in affinity for penicillin or a reduction in the amount of a PBC protein, or both, are the probable explanations of penicillin resistance in these strains.